2015
DOI: 10.5966/sctm.2015-0057
|View full text |Cite
|
Sign up to set email alerts
|

Perivascular Mesenchymal Stem Cells From the Adult Human Brain Harbor No Instrinsic Neuroectodermal but High Mesodermal Differentiation Potential

Abstract: Brain perivascular cells have recently been identified as a novel mesodermal cell type in the human brain. These cells reside in the perivascular niche and were shown to have mesodermal and, to a lesser extent, tissue-specific differentiation potential. Mesenchymal stem cells (MSCs) are widely proposed for use in cell therapy in many neurological disorders; therefore, it is of importance to better understand the "intrinsic" MSC population of the human brain. We systematically characterized adult human brain-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 38 publications
2
14
0
Order By: Relevance
“…During adipogenic and osteogenic differentiation, various mutations in LMNA gene which encodes for the nuclear lamin A/C protein influenced the differentiation efficacy of BM-MSCs in a mutation-specific manner and promoted unique gene expression patterns (Malashicheva et al, 2015). Comparative transcriptome analysis revealed that the adult human brain-derived perivascular MSCs holds comparable differential potential to that of the human brain-derived NSCs and the human BM-MSCs; thus highlighting the potential of perivascular MSCs for therapeutic use similar to neural and bone-marrow stem cells (Lojewski et al, 2015).…”
Section: Tracking Cell Differentiationmentioning
confidence: 95%
“…During adipogenic and osteogenic differentiation, various mutations in LMNA gene which encodes for the nuclear lamin A/C protein influenced the differentiation efficacy of BM-MSCs in a mutation-specific manner and promoted unique gene expression patterns (Malashicheva et al, 2015). Comparative transcriptome analysis revealed that the adult human brain-derived perivascular MSCs holds comparable differential potential to that of the human brain-derived NSCs and the human BM-MSCs; thus highlighting the potential of perivascular MSCs for therapeutic use similar to neural and bone-marrow stem cells (Lojewski et al, 2015).…”
Section: Tracking Cell Differentiationmentioning
confidence: 95%
“…The relevance of MSCs for the bone marrow homeostasis is underpinned by the observation that co‐administration of autologous MSCs facilitated HSC engraftment after myeloablative treatments . Similarly, MSCs interact with tissue‐specific stem cells and functional parenchymal cells in various other organs including bone, lung and blood vessels …”
Section: Introductionmentioning
confidence: 99%
“…In addition, pericytes have been reported to possess multipotent potential, differentiating down the mesenchymal lineages in vitro . Recent reports have suggested that mesenchymal stromal cells (MSCs) may represent a subclass of pericytes following their identification in the perivascular tissue of almost all organs of the human body, including the adult brain . In vitro, MSCs, in addition to their multipotency are characterized by their capacity to exert strong immunosuppressive and trophic properties, mainly by the secretion of soluble factors .…”
Section: Introductionmentioning
confidence: 99%